2015
DOI: 10.3402/ecrj.v2.26721
|View full text |Cite
|
Sign up to set email alerts
|

Fabry disease, respiratory symptoms, and airway limitation – a systematic review

Abstract: BackgroundFabry disease is an X-linked disorder caused by a deficiency of the lysosomal enzyme α-galactosidase A, resulting in accumulation of glycosphingolipids in multiple organs, primarily heart, kidneys, skin, CNS, and lungs.Materials and methodA systematic literature search was performed using the PubMed database, leading to a total number of 154 hits. Due to language restriction, this number was reduced to 135; 53 papers did not concern Fabry disease, 19 were either animal studies or gene therapy studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…Male and female patients with Fabry disease can develop pulmonary manifestations, usually presenting as shortness of breath during exercise, chronic cough, and wheezing, with many patients having obstructive airway limitation [173,174]. It is not clear how much pulmonary involvement may contribute to cause dyspnoea in patients with Fabry disease, as asthma and chronic obstructive pulmonary disease are also prevalent in the general population [174].…”
Section: Pulmonary Manifestationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Male and female patients with Fabry disease can develop pulmonary manifestations, usually presenting as shortness of breath during exercise, chronic cough, and wheezing, with many patients having obstructive airway limitation [173,174]. It is not clear how much pulmonary involvement may contribute to cause dyspnoea in patients with Fabry disease, as asthma and chronic obstructive pulmonary disease are also prevalent in the general population [174].…”
Section: Pulmonary Manifestationsmentioning
confidence: 99%
“…Male and female patients with Fabry disease can develop pulmonary manifestations, usually presenting as shortness of breath during exercise, chronic cough, and wheezing, with many patients having obstructive airway limitation [173,174]. It is not clear how much pulmonary involvement may contribute to cause dyspnoea in patients with Fabry disease, as asthma and chronic obstructive pulmonary disease are also prevalent in the general population [174]. On the other hand, although evidence on the effect of ERT on pulmonary involvement is limited, several case reports and an observational study suggest that symptoms can be improved or at least stabilized by treatment [175][176][177].…”
Section: Pulmonary Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 The benefits of early treatment, before irreversible tissue injury occurs, should be balanced against the burden of biweekly infusions in very young individuals. In a recent pediatric randomized controlled trial (RCT), Fabry arteriopathy and segmental effacement of podocyte foot processes were found in all biopsied FD patients with normal GFR and urinary albuminto-creatinine ratio (UACR) < 30 mg/g, 31 suggesting early ERT as well as the role of b2-agonists 86,114 Provide uniform description and categorization of study populations in future reports on the efficacy of therapy, including genotype, phenotype, sex, and age at initiation of therapy Conduct long-term outcome studies of (pediatric) patients who started ERT when asymptomatic or paucisymptomatic Collect histologic evidence of ERT-induced clearance of Gb3 in longlived cells: vascular smooth muscle cells, cardiomyocytes, podocytes Conduct studies on the pathophysiology and treatment of gastrointestinal involvement and lymphedema Develop more sensitive patient-reported outcome measures ERT, enzyme replacement therapy; FD, Fabry disease.…”
Section: Initiation Of Ertmentioning
confidence: 99%
“…A mixture of different etiologic mechanisms of obstructive and restrictive pulmonary symptoms has been reported in several small studies and case reports, and a recent systematic review could not identify consistent findings in the literature. 86 A registry study concluded that 23 of 67 patients had airway obstruction similar to chronic obstructive pulmonary disease, and obstructive lung disease has been m e e t i n g r e p o r t reported to be up to 10 times more prevalent in people with FD than in the general population.…”
Section: Pulmonary Diseasementioning
confidence: 99%